Recent advances in the extraction, chemical composition, therapeutic potential, and delivery of cardamom phytochemicals - Abdullah,; Ahmad, Naveed; Tian, Wenni; Zengliu, Song; Zou, Yucheng; Farooq, Shahzad; Huang, Qingrong; Xiao, Jie (Frontiers in Nutrition, 2022)
Dietary phytochemicals including plant-derived alkaloids, carotenoids, organosulfur compounds, phenolics, and phytosterols, are health-promoting bioactive compounds that help in the prevention and mitigation of chronic diseases and microbial infections beyond basic nutrition supply. This article covers recent advances in the extraction, chemical composition, therapeutic potential (nutraceutical and antimicrobial), and delivery of black and green cardamom-derived phytochemicals. In recent years, advance extraction techniques (e.g., enzyme-assisted-, instant controlled pressure drop-, microwave-assisted-, pressurized liquid-, sub-critical-, supercritical fluid-, and ultrasound-assisted extractions) have been applied to obtain phytochemicals from cardamom. The bioactive constituents identification techniques, specifically GC-MS analysis revealed that 1,8-cineole and α-terpinyl acetate were the principle bioactive components in black and green cardamom. Regarding therapeutic potential, research findings have indicated desirable health properties of cardamom-derived phytochemicals, including antioxidant-, anti-hypercholesterolemic, anti-platelet aggregation, anti-hypertensive, and gastro-protective effects. Moreover, antimicrobial investigations revealed that cardamom phytochemicals effectively inhibited growth of pathogenic microorganisms (bacteria and fungi), biofilm formation inhibition (Gram-negative and Gram-positive bacteria) and bacterial quorum sensing inhibition. Encapsulation and delivery vehicles, including microcapsules, nanoparticles, nanostructured lipid carriers, and nanoliposomes were effective strategies to enhance their stability, bioavailability and bioefficacy. Cardamom had promising antioxidant and antimicrobial potentials, thus could be used as food additive to increase shelf life, inhibit oxidative rancidity and confer pleasant aroma to commercial edibles as well as mitigate lifestyle related chronic diseases (e.g., cardiovascular and gastrointestinal diseases).